PESAN DAKWAH DALAM AKUN TIKTOK @heyouw0 SEBAGAI MEDIA DAKWAH - Audina, Farah; N. Abddurrazaq, Muhammad; srof Fitri, Ahmad A (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
This study examines the da'wah messages on the TikTok account @heyouw0 as a medium for da'wah. The TikTok account of Agam Fachrul, commonly known by the username @heyouw0, is one of the accounts that conveys da'wah through TikTok, a social media platform with a large user base in Indonesia. Preaching through social media is an example of adapting positively to modern times, and this can be seen on the @heyouw0 account. Almost all of its content contains da'wah messages, making it a relevant da'wah medium in today’s digital era. The purpose of this study is to understand how the da'wah messages related to Aqidah (faith), Akhlak (morals), and Sharia (Islamic law) are conveyed in the videos posted on this TikTok account. Another goal is to identify the most dominant da'wah message on the TikTok account @heyouw0. This research uses a qualitative method with observation and documentation techniques to analyze videos on the TikTok account @heyouw0, followed by analyzing documents related to the Aqidah, Akhlak, and Sharia messages found on this account. The findings from Agam Fachrul Samudra’s TikTok account indicate that the uploaded videos contain messages encouraging Muslims to believe in Allah as the Lord of the universe, maintain tolerance, foster relationships, be cautious in choosing friends, observe moderation in joking, and show respect toward others. Additionally, the messages emphasize helping others in good deeds and avoiding all forms of immoral activities. Keywords: TikTok Content, Da'wah Messages, Aqidah, Morals, Sharia